I need steps broken down so that I can understand how to solve these kinds of problems.

## Answers (2)

Here's another problem, but similar :

x2+7x+12=0

x^(2)+7x+12=0

For a polynomial of the form x^(2)+bx+c, find two factors of c (12) that add up to b (7). In this problem 4*3=12 and 4+3=7, so insert 4 as the right hand term of one factor and 3 as the right-hand term of the other factor.

(x+4)(x+3)=0

Set each of the factors of the left-hand side of the equation equal to 0.

x+4=0_x+3=0

Since 4 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 4 from both sides.

x=-4_x+3=0

Set each of the factors of the left-hand side of the equation equal to 0.

x=-4_x+3=0

Since 3 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 3 from both sides.

x=-4_x=-3

The complete solution is the set of the individual solutions.

x=-4,-3

I tried my best! Sorry if it didn't help or make any sense.

The only way I can do this:

x^2 + x - 3/4 = 0

First I draw this out:

(x + _)(x - _)=0 Because that is the only way to get a negative third value and a positive first. ALso the (x+_) must be larger than the (x - _) to produce a positive second value.

(x + 1.5)(x - .5) = 0 Because this is the only values that multiplied equal .75 and added equal 1

Thus (x = -1.5 and +.5) Based on the fact that either will make the left equal to the right (0=0)